2014
DOI: 10.5014/ajot.2014.009704
|View full text |Cite
|
Sign up to set email alerts
|

Content Analysis of Five Occupational Therapy Journals, 2006–2010: Further Review of Characteristics of the Quantitative Literature

Abstract: OBJECTIVE. To analyze the content of publications in 5 occupational therapy journals to determine the strengths and weaknesses of the literature base from 2006 to 2010. METHOD. A content analysis for 2006 through 2010 of the American Journal of Occupational Therapy (AJOT), Australian Occupational Therapy Journal (AOTJ), British Journal of Occupational Therapy (BJOT), Canadian Journal of Occupational Therapy (CJOT), and Scandinavian Journal of Occupational Therapy (SJOT) was completed. RESULTS. AJOT and SJOT ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
8
1
Order By: Relevance
“…Mountain (1997) also noted in a content review of articles published in BJOT that they primarily focused on clinical work with a strong representation of physical disabilities. In contrast to the findings of the current study, Pearl et al (2014) reported that the majority of BJOT articles published from 2006 to 2010 focused on education.…”
Section: Publication Outputscontrasting
confidence: 55%
See 2 more Smart Citations
“…Mountain (1997) also noted in a content review of articles published in BJOT that they primarily focused on clinical work with a strong representation of physical disabilities. In contrast to the findings of the current study, Pearl et al (2014) reported that the majority of BJOT articles published from 2006 to 2010 focused on education.…”
Section: Publication Outputscontrasting
confidence: 55%
“…Neurology and mental health were also two other common subject areas in which British occupational therapy authors published. Pearl et al (2014), in a comparison of five occupational therapy journals, determined that the contents of the BJOT articles covered a range of topics, including education, mental health, community, physical disabilities, and pediatrics.…”
Section: Web Of Science Core Collection Subject Categories and Journalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical research (qualitative, quantitative, and mixed-methods research) published between 2013 and 2017 in which the majority of participants were older than 65 years (when mean age was reported in the articles it had to be 65 years or higher, or participants described as older adults) was included. A five-year period has been used in similar reviews of articles published in occupational therapy journals [8,11]. This five-year period was thought to be suitable to avoid bias in the results due to special issues that could have skewed the results (for example, proportions of published articles, or certain topics).…”
Section: Inclusion Of Articlesmentioning
confidence: 99%
“…Literature reviews are used to synthesize existing research, what has been done, what is already known or what gaps exist in knowledge about a certain topic [10]. Literature reviews can also be used to present the characteristics of articles published in a certain research field [11] or to review certain areas or topics of articles published in occupational therapy journals [6,8,9,[12][13][14]. Previous research concerning articles published in the field of occupational therapy has analyzed the references used in publications [6,15,16], or quantified the influence of scholarly activities [17][18][19].…”
Section: Introductionmentioning
confidence: 99%